2018
DOI: 10.1016/j.ultsonch.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound effects based on simulation of milk processing properties

Abstract: Efficient reconstitution followed by fermentation of nonfat (skimmed) dry milk is one of the most important aspects in manufacturing of various dairy products. As a first stage, dry milk is normally being reconstituted using conventional approaches such as heating and stirring the mixture. Nevertheless, we demonstrated, that low-frequency (22 ± 1.65 kHz) ultrasound can be used as an alternative to the traditional methods of milk recovery. Low-frequency ultrasound was applied during pre-fermentation stage to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The polysaccharides were separated with acetone and complete hydrolysis of them was done by sulphuric acid (1 M) for 2 h at 100 °C and following neutralisation by sodium hydroxide. The polysaccharide content was measured as per glucose calibration curve (Potoroko et al , ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polysaccharides were separated with acetone and complete hydrolysis of them was done by sulphuric acid (1 M) for 2 h at 100 °C and following neutralisation by sodium hydroxide. The polysaccharide content was measured as per glucose calibration curve (Potoroko et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound treatment is one of the emerging non‐thermal technologies in food processing, which can be used to minimise processing, improve quality, ensure microbial safety and extend shelf‐life without altering nutritional and sensory properties of food products (Potoroko et al , ). Electroporation (the formation of pores in the cell wall), which leads to increased cell permeability, has been stated as the main mechanism of ultrasound treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that the food matrix plays an influential role in inactivating microorganisms by US. Lactose has been suggested to increase the resistance of microorganisms to the US by stabilizing bacterial membranes and accumulating compatible solutes [37] . Fats also play a protective role for fungus because they can increase the resistance of fungus to inactivation treatments either by decreasing the water activity (aw) of the system or by dehydrating cells immersed in the lipid phase of the system [2] .…”
Section: Factors Affecting Fungal Inactivationmentioning
confidence: 99%
“…Применяя различные воздействия (ультразвуковые, электрические и магнитные поля, СВЧ и т.п. ), можно изменять свойства пищевых систем [1][2][3][4][5][6]. Инновационным вектором развития в кондитерском производстве считается применением теории механо-химических процессов в смесях жидких и твердых фаз.…”
Section: Introductionunclassified